Пропавшие: [роман] / Крис Муни ; [пер. Ю. Лелюк] - Муни Крис (Клуб семейного досуга, 2008)
Экземпляры: аб. (2009) / Инвентарный номер: 52853 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: М 90 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44